Characterization of a novel mCH3 conjugated anti-PcrV scFv molecule - Samira Komijani; Elham Bayat; Elham Rismani; Soma Hosseini; Reza Moazzami; Leila Nematollahi; Soroush Sardari; Yeganeh Talebkhan; Fatemeh Davami; Farzaneh Barkhordari; Fakhrisadat Hosseini; Hoda Jahandar (Scientific Reports, 2021)
Abstract Pseudomonas aeruginosa (PA) is a leading cause of nosocomial infections and death in cystic fibrosis patients. The study was conducted to evaluate the physicochemical structure, biological activity and serum stability of a recombinant anti-PcrV single chain variable antibody fragment genetically attached to the mCH3cc domain. The stereochemical properties of scFv-mCH3 (YFL001) and scFv (YFL002) proteins as well as molecular interactions towards Pseudomonas aeruginosa PcrV were evaluated computationally. The subcloned fragments encoding YFL001 and YFL002 in pET28a were expressed within the E. coli BL21-DE3 strain. After Ni–NTA affinity chromatography, the biological activity of the proteins in inhibition of PA induced hemolysis as well as cellular cytotoxicity was assessed. In silico analysis revealed the satisfactory stereochemical quality of the models as well as common residues in their interface with PcrV. The structural differences of proteins through circular dichroism spectroscopy were confirmed by NMR analysis. Both proteins indicated inhibition of ExoU positive PA strains in hemolysis of red blood cells compared to ExoU negative strains as well as cytotoxicity effect on lung epithelial cells. The ELISA test showed the longer serum stability of the YFL001 molecule than YFL002. The results were encouraging to further evaluation of these two scFv molecules in animal models.